2001
DOI: 10.1002/1521-3773(20011105)40:21<4077::aid-anie4077>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene-Bound Tetrafluorophenylbis(triflyl)methane as an Organic-Solvent-Swellable and Strong Brønsted Acid Catalyst The authors thank Mr. Shoichi Kondo for the single-crystal X-ray analysis. Sodium triflate was generously donated by Central Glass Co., Ltd., Japan. The authors also acknowledge Dr. Yuko Wasada and Dr. Manabu Kubota for their helpful discussions on the theoretical calculations.

Abstract: Several advantages over inorganic solid acids such as zeolites and perfluororesinsulfonic acids such as Nafion are offered by the new reusable polystyrene‐bound catalyst 1: a broader range of applications, improved yields, improved selectivity, and milder reaction conditions. Tf = F3CSO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Introducing triflyl groups to organic molecules increases the acidity of the neighboring α‐hydrogens, an effect that rises with the number of triflyl groups. As a result, the maximum possible number of triflyl groups often confers highest acidity to a molecule . Examples for strong acids containing triflyl moieties are triflic acid (TfOH), triflimide (Tf 2 NH), and tris(triflyl)methane (Tf 3 CH) with p K a values (in dichloroethane, relative to picric acid) of −11.4 (TfOH), −11.9 (Tf 2 NH), and an estimated −16.4 (Tf 3 CH) .…”
Section: Methodsmentioning
confidence: 99%
“…Introducing triflyl groups to organic molecules increases the acidity of the neighboring α‐hydrogens, an effect that rises with the number of triflyl groups. As a result, the maximum possible number of triflyl groups often confers highest acidity to a molecule . Examples for strong acids containing triflyl moieties are triflic acid (TfOH), triflimide (Tf 2 NH), and tris(triflyl)methane (Tf 3 CH) with p K a values (in dichloroethane, relative to picric acid) of −11.4 (TfOH), −11.9 (Tf 2 NH), and an estimated −16.4 (Tf 3 CH) .…”
Section: Methodsmentioning
confidence: 99%
“…159 Hu's group reported that the TfOH-catalyzed Friedel−Crafts alkylation of electron-rich alkene 145 with 3-diazooxindoles 144 furnished 3-aryloxindoles 146 in good to high yields (Scheme 53). 160 A deuterium-labeling study elucidated that this aromatic Chem. Rev.…”
Section: C−h Bond Functionalizationmentioning
confidence: 99%
“…Most of the ILs consist alkyl or aryl nitrogen containing cations such as ammonium and imidazolium, benzimidazolium, pyridinium, etc. respectively . ILs are also useful as environmental‐benign catalysts.…”
Section: Introductionmentioning
confidence: 99%